Graphene slurry based passive Q-switcher in erbium doped fiber laser - Siti Nur Fatin Zuikafly; Nor Farhah Razak; Rizuan Mohd Rosnan; Sulaiman Wadi Harun; Fauzan Ahmad (Institute of Advanced Engineering and Science, 2019)
In this work, a Graphene slurry based passive Q-switcher fabricated from Graphene-Polylactic acid (PLA) filament which is used for 3D printing. To produce the Graphene slurry, the diameter of the filament was reduced and Tetrahydrofuran (THF) was used to dissolve the PLA. The Graphene-THF suspension was drop cast to the end of a fiber ferrule and the THF then evaporated to develop Graphene slurry based SA which is integrated in fiber laser cavity. At threshold input pump power of 30.45 mW, a Q-switched Erbium-doped fiber laser (EDFL) can be observed with the wavelength centered at 1531.01 nm and this remained stable up to a pump power of 179.5 mW. As the pump power was increased gradually, an increase in the repetition rates was recorded from 42 kHz to 125 kHz, while the pulse width was reduced to 2.58 μs from 6.74 μs. The Q-switched laser yielded a maximum pulse energy and peak power of 11.68 nJ and 4.16 mW, respectively. The proposed Graphene slurry based saturable absorber also produced a signal-to-noise ratio of 44 dB indicating a stable Q-switched pulsed laser.